Fuzzy Analytical Hierarchy Process: Pendekatan dalam Sistem Pendukung Keputusan Lokasi Coffee Shop - Aini, Qurrotul; Zulfiandri, Zulfiandri; Cholis, Nur (Universitas Islam Sumatera Utara, 2022)
The commitment of the Government of Indonesia in the development of the economic sector is economic development based on the participation of the wider community as business actors. The largest proportion of business actors owned by Indonesia itself is from Micro, Small and Medium Enterprises (MSMEs). Coffee Shop is one of the MSMEs that is currently in high demand in big cities, particularly the city of Jakarta. MSME business actors make careful considerations in determining the location of the coffee shop. This study aims to build a decision support system by applying a fuzzy analytical hierarchy process at the level of importance of criteria and full factorial methods to determine the best alternative. The location determination is based on the criteria of population, income, location area, competitor density, location position, visibility, traffic pattern, parking area, internet connection, and construction plan. The result of this research is a decision support system that is able to recommend the location of the coffee shop with the best value of 0.705 until the last location is worth 0.421.Komitmen Pemerintah Indonesia dalam pengembangan bidang ekonomi adalah pembangunan ekonomi yang berbasis partisipasi masyarakat luas sebagai pelaku usaha. Proporsi pelaku usaha terbesar yang dimiliki Indonesia sendiri adalah dari Usaha Mikro, Kecil dan Menengah (UMKM). Coffee Shop merupakan salah satu UMKM yang sedang ramai diminati oleh para pelaku usaha di kota-kota besar khususnya kota Jakarta. Para pelaku usaha UMKM melakukan pertimbangan yang matang dalam menentukan lokasi coffee shop. Penelitian ini bertujuan membangun sistem pendukung keputusan dengan menerapkan fuzzy analytical hierarchy process pada tingkat kepentingan kriteria dan metode full factorial untuk menentukan alternatif terbaiknya. Adapun penentuan lokasi berdasarkan kriteria populasi, pendapatan, luas lokasi, kepadatan kompetitor, posisi lokasi, visibilitas, pola lalu lintas, area parkir, koneksi internet dan rencana konstruksi. Hasil penelitian ini adalah sistem pendukung keputusan yang mampu merekomendasikan lokasi coffee shop dengan nilai terbaik 0,705 hingga lokasi urutan terakhir bernilai 0,421.